Hubungan Konformitas Teman Sebaya dengan Perilaku Prososial Berdasarkan Jenis Kelamin pada Siswa SMA - Siska Muliasari; Githa Gemisa; Nuraisah Rizki Syahputri; Muhammad Aulia; Wahidah Fitriani (Scidacplus, 2026)
This study aimed to determine the relationship between peer conformity and prosocial behavior based on gender among senior high school students. The study employed a quantitative approach with a correlational research design. The study population comprised all students at SMA Negeri 2 Lubuk Basung, and the sample was selected through proportional random sampling. The research instruments were Likert-scale questionnaires measuring peer conformity and students’ prosocial behavior. Data were analyzed using descriptive statistics, Pearson Product-Moment correlation, and an independent-samples t-test. The results revealed a positive and significant relationship between peer conformity and students’ prosocial behavior. Students who showed higher positive conformity toward their peer groups tended to demonstrate higher prosocial behavior, such as helping, sharing, cooperating, and showing concern for others. In addition, differences in prosocial behavior were found by gender, with female students showing higher levels than male students. These findings indicate that peer influence plays an important role in shaping adolescents’ social behavior in the school environment. This study contributes to the field of guidance and counseling, particularly in developing social guidance services to enhance students’ prosocial behavior through positive peer influence. Future studies are recommended to examine other factors influencing prosocial behavior, such as parenting style, empathy, and social media use.